Tetraoxa-Diphosphaspiro Derivative as Suppressor for Microvia Filling by Copper Electroplating in Acidic Solution. Issue 14 (1st January 2017) - Tao, Zhihua.; He, Wei.; Li, Jing; Wang, Shouxu; Chen, Yuanming; Ai, Kehua; Peng, Yongqiang; Hong, Yan
Abstract : In this work, a novel suppressor, tetraoxa-diphosphaspiro derivative (MPTD) was applied in copper electroplating solution for microvia filling. The suppression function of MPTD and its synergistic effect with other additives during copper electroplating were investigated by means of galvanostatic measurements, cyclic voltammetric and EIS. The surface morphology of electrodeposition experiments was examined using a scanning electron microscope (SEM). The filling performance was evaluated by observing the obtained cross-sectional views of the microvias after electroplating. The galvanostatic measurements results revealed the strong synergistic inhibitory effect on both MPTD and chloride ions. In addition, the results from cyclic voltammetry (CV) measurements indicates that the concentration of the plating additives (such as suppressor, accelerator and leveler) at fixed relative proportion required an optimal Cl − concentration in the plating bath to reach the strongest suppression strength. The negative values of Δ G 0 ads suggest that the synergistic inhibitory effect of Cl − onto the cathode surface is a spontaneous process. The values of the standard free energy of adsorption reveals that Cl − adsorbed on Cu surface involves both chemisorption and physisorption. This improved copper plating solution composed of CuSO4, H2 SO4, MPTD, SPS, chloride ions, and JGB is optimal and capable to perform bottom-up copper filling of microvias.